Genetic mechanism of high-quality shale gas reservoirs in the Wufeng–LongmaxiFms in the Sichuan Basin - Haikuan Nie; Zhiliang He; Guangxiang Liu; Wei Du; Ruyue Wang; Guangrong Zhang (Natural Gas Industry B, 2021)
The Upper Ordovician WufengFm and the Lower Silurian LongmaxiFm are important strata for shale gas exploration and development in the Sichuan Basin, but the genetic mechanism, evolutionary history and the controlling effect of mineral diagenetic evolution on the formation of shale gas reservoirs are not clear. In this paper, the evolution history of organic matter pores and the diagenetic evolution of minerals were analyzed based on the analysis of petrology, mineralogy and organic geochemistry, combined with basin simulation and practical shale gas exploration and development. Then, the types and genetic mechanisms of high-quality shale gas reservoirs were discussed, and the development intervals of high-quality shale gas reservoirs were determined. And the following research results are obtained. First, the shale gas development intervals of Wufeng–LongmaxiFms in the Sichuan Basin are mainly dominated by siliceous shale, limy siliceous shale and clayey shale. Rock type has an important controlling effect on the types and characteristics of shale reservoir space. Siliceous shale and limy siliceous shale have the highest reservoir capacity with the most developed organic pores. Second, the diagenetic evolution of minerals controls the formation of shale gas reservoirs. Biogenic silica, formed in the early diagenetic stage, together with terrestrial detrital silica and pyrite, constitutes particle support lattices in the form of microcrystalline aggregates, so as to resist the compaction effectively and preserve a great number of residual intergranular pores, which is beneficial to the formation of high-quality shale gas reservoirs. Third, siliceous shale in the WF2–LM4 graptolite zone (from WufengFm to the bottom of LongmaxiFm) presents a high-quality reservoir genetic mechanism of “multicellular algae controlling hydrocarbon source, biogenic silica controlling framework, and co-evolution controlling a high-quality reservoir”. In conclusion, the siliceous shale and limy siliceous shale in the WF2–LM4 graptolite zones are the main development intervals of high-quality shale gas reservoirs in the Sichuan Basin. It is also a valuable reference for the Upper Ordovician-Lower Silurianshale gas exploration and development in other countries and regions worldwide.